2010
DOI: 10.1186/1471-2261-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to cardiovascular effects of dihydrocapcaicin in resuscitated rats. Cardiovascular effects of dihydrocapsaicin

Abstract: BackgroundSurvivors of a cardiac arrest often have persistent cardiovascular derangements following cardiopulmonary resuscitation including decreased cardiac output, arrhythmias and morphological myocardial damage. These cardiovascular derangements may lead to an increased susceptibility towards the external and internal environment of the cardiovascular system as compared to the healthy situation.MethodsHere we tested the hypothesis that the cardiovascular system in healthy rats and rats resuscitated from a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
1
9
2
Order By: Relevance
“…In contrast to our findings with subcutaneous delivery, intravenous infusion of DHC showed a dose-dependent increase in mean BP and HR in rats (14). In the same study, however, the authors also reported that 2 of 6 rats showed transient hypotension and bradycardia (14). Intravenous infusion of capsaicin in dogs, at doses lower than 0.1 mg/kg, did not show any effect on BP and HR while doses higher than 0.3 mg/kg showed a transient rise in BP and HR (7).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast to our findings with subcutaneous delivery, intravenous infusion of DHC showed a dose-dependent increase in mean BP and HR in rats (14). In the same study, however, the authors also reported that 2 of 6 rats showed transient hypotension and bradycardia (14). Intravenous infusion of capsaicin in dogs, at doses lower than 0.1 mg/kg, did not show any effect on BP and HR while doses higher than 0.3 mg/kg showed a transient rise in BP and HR (7).…”
Section: Discussioncontrasting
confidence: 56%
“…Interestingly, the effect of capsacinoids on cardiovascular function may vary depending on the delivery route. In contrast to our findings with subcutaneous delivery, intravenous infusion of DHC showed a dose-dependent increase in mean BP and HR in rats (14). In the same study, however, the authors also reported that 2 of 6 rats showed transient hypotension and bradycardia (14).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It is, thus, tempting to speculate that using pharmacological TRPV1 agonists to produce or enhance therapeutic hypothermia may bring an additional benefit of blunting tachycardia, limiting the load on the heart and preventing cardiac tachyarrhythmias. However, TRPV1 agonists seem to have complex and variable effects on the cardiovascular system at baseline conditions in the absence of cooling (4,9,13,35,36). Since there is no clear and unified picture of how TRPV1 activation affects heart function, this area deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Several endogenous and exogenous TRPV1 agonists have been identified, some of which can modulate body temperature. For instance, dihydrocapsaicin induces a sustainable mild hypothermia in rats, cynomologus monkeys and young cattle [59]. Rinvanil is a synthetic TRPV1 agonist that possesses ultrapotent activating effects [60].…”
Section: Transient Receptor Potential Vanilloid 1 (Trpv1)mentioning
confidence: 99%